Effects of irrigation and fertilization on different potato varieties growth, yield and resources use efficiency in the Northwest China - Xing, Yingying; Zhang, Teng; Jiang, Wenting; Li, Peng; Shi, Peng; Xu, Guoce; Cheng, Shengdong; Cheng, Yuting; Fan, Zhang; Wang, Xiukang (Agricultural water management, 2022)
The scarcity of irrigation water has now become the main constraint for crop production globally. Potato growth in arid and semiarid regions is facing increasing challenges due to water deficit. Potato productivity is generally influenced by water and fertilizer, and the requirements for these factors vary depending on the soil type and potato variety. Field experiments were conducted during 2019–2020 to select the suitable potato varieties with the best combination of irrigation and fertilization levels. The three irrigation amounts were W1 (100% crop evapotranspiration (ETC)), W2 (80% ETC) and W3 (60% ETC). The three fertilizer rates were F1 (N–P2O5–K2O, 240–120–300 kg ha−1), F2 (180–90–225 kg ha−1) and F3 (120–60–150 kg ha−1). The three locally cultivated potato varieties were V1 (Feiurita), V2 (Xiapoti), and V3 (Yushu 4). The results showed that irrigation amount, fertilizer amount and potato variety had significant effects on potato growth, yield, quality and water and fertilizer productivity. The average potato yield and irrigation water use efficiency (IWUE) in Feiurita were 12.5% (11.9%) and 14.2% (13.3%) higher than those in Xiapoti in 2019 (2020), respectively. On average, the tuber yield and partial factor productivity (PFP) in W1 were 27.8% (35%) and 26.8% (34.7%) higher than those in W3 in 2019 (2020), respectively. Tuber yield, IWUE and polyphenol oxidase activity (POA) were most subject to irrigation amount, followed by potato variety and fertilizer rate. Potato tuber yield was significantly correlated with soil available potassium, soil actinomycete quantity, soil catalase activity, and soil sucrase activity (SSA). The W2F3V1 treatment had the highest PFP, starch content, reducing sugar content, and vitamin C content (VC), and the tuber yield and crude protein content were relatively high. The W3F2V1 treatment had the highest IWUE and vitamin C, and the starch content and POA were relatively high. Among them, the soil actinomycete quantity, soil cellulose decomposition bacteria quantity (SCDBQ), soil catalase activity, soil urease activity (SUA), and SSA in the W2F3V1 and W3F2V1 treatments were moderate. The W2F3V1 and W3F2V1 treatments are recommended as the best water and fertilizer management in sandy loam soils in Northwest China. •Tuber yield was most subject to irrigation, followed by variety and fertilizer•Soil pH and soil conductivity significantly affected vitamin C content•Increasing irrigation amount can reduce soil actinomyces and increase sucrase•Soil cellulose decomposition bacteria significantly affected reducing sugar